REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION (rTMS) AS A NON-INVASIVE NEUROMODULATION FOR THE SPECTRUM OF NON-MOTOR SYMPTOMS IN PARKINSON’S DISEASE: A SYSTEMATIC REVIEW - Izzati Paramadina; Ninda Pradani Futana; Sulistyani (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Non-motor symptoms are an essential component of Parkinson’s disease (PD) and represent a major contributor to disability and quality of life. Repetitive transcranial magnetic stimulation (rTMS) has been explored as a non-invasive adjunctive therapy; however, evidence remains heterogeneous and limited to specific symptom domains. Objective: This systematic review aimed to synthesize randomized controlled trial (RCT) evidence on the efficacy and safety of rTMS for non-motor symptoms in PD. Methods: RCTs published between 2017 and 2026 were identified from PubMed, Nature Portfolio, and SpringerLink. Twelve studies with PD were included, comparing active rTMS with sham. Outcomes encompassed sleep disturbances, depression, anxiety, pain, apathy, constipation, and cognitive impairment. Risk of bias was evaluated using Cochrane RoB 2.0. Results: Twelve RCTs (566 patients) with PD were included. rTMS showed the most consistent benefits for sleep disturbances and depressive symptoms, particularly with low-frequency stimulation targeting the right dorsolateral prefrontal cortex (DLPFC). Evidence for anxiety, pain, apathy, and cognitive outcomes was moderate and variable, with effects dependent on stimulation parameters and cortical targets; cognitive benefits were largely confined to executive domains. Preliminary evidence suggested a potential emerging role for rTMS in improving constipation via prefrontal modulation of the gut–brain axis. Overall, rTMS was well tolerated, with only mild and transient adverse events reported and no serious safety concerns. Conclusion: rTMS is a safe and well-tolerated neuromodulation approach with potential domain-specific benefits for non-motor symptoms in PD, particularly sleep and depression. This review contributes to the current understanding of symptom-targeted rTMS applications in PD.